2022
DOI: 10.1021/acs.jpcc.2c05816
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport through Polymer-Linked Gold Nanoparticles

Abstract: Polymer–nanoparticle networks have potential applications in molecular electronics and nanophononics. In this work, we use all-atom molecular dynamics to reveal the fundamental mechanisms of thermal transport in polymer-linked gold nanoparticle (AuNP) dimers at the molecular level. Attachment of the polymers to AuNPs of varying sizes allows the determination of effects from the flexibility of the chains when their ends are not held fixed. We report heat conductance (G) values for six polymersviz. polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The tree polymers in these systems are unstretched; see schemes in Figure a,b. Previously, we had found that unstretched polymers have converged heat flux values, ,, and thus they are sufficient to reveal the tree structure effect on heat transfer. After the relaxation step, the nonequilibrium MD simulation method is applied to calculate the heat flux through the tree networks.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The tree polymers in these systems are unstretched; see schemes in Figure a,b. Previously, we had found that unstretched polymers have converged heat flux values, ,, and thus they are sufficient to reveal the tree structure effect on heat transfer. After the relaxation step, the nonequilibrium MD simulation method is applied to calculate the heat flux through the tree networks.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In determining heat fluxes, we calculate the heat conductance , G and not the conventional thermal conductivity κ because the heat transfer mechanism is not diffusiveas might be required for the latterat the nanoscale. In our previous work, we found that heat conductance ( G ) of a linear PE chain with 100 carbons C100 is 24.8 ± 2.4 pW/K . Though not shown, we converted our results from G to κ and confirmed agreement with Zhang and Luo for unstretched unbranched PE chains.…”
mentioning
confidence: 86%
See 3 more Smart Citations